First case report of bacteremia caused by Bilophila wadsworthia in China, and literature review - Fangrong Gan; Shuang Luo; Xiaoxun Wei; Shuguang Zuo (BMC Infectious Diseases)
Abstract Bilophila wadsworthia is rarely found in the bloodstream. We report the first case of bloodstream infection caused by B. wadsworthia in a diabetic foot patient in China. B. wadsworthia is a normal component of the human intestinal microbiota, and a history of diarrhea may contribute to its translocation into the bloodstream. Due to the slow growth of B. wadsworthia, prolonged incubation was essential for its detection. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) enabled rapid identification of the pathogen. Early initiation of Piperacillin/Tazobactam therapy resulted in a favorable clinical outcome.